Validation of three names of nothospecies in Malinae, Rosaceae - Mezhenskyj, V.M. (Український ботанічний журнал, 2013)
Three names in three nothogenera, ×Cydolus, ×Pyralus, and ×Sorbaronia (Malinae, Rosaceae), have not been validly published because the types representing two or three gatherings were
cited for each taxon. These three names are validated here, with
one specimen designated as the holotype for each nothospecies. Три назви в нотородах ×Cydolus, ×Pyralus, ×Sorbaronia (Malinae, Rosaceae) не були дійсно обнародувані, тому що типами для кожного таксона позначалися два або три збори. Здійснено обнародування назв ×Sorbaronia kovalevii Mezhenskyj, ×Cydolus rudenkoana Mezhenskyj, ×Pyralus kursakovii Mezhenskyj із зазначенням одного збору, що визначений як голотип для кожного нотовиду. Три названия в нотородах ×Cydolus, ×Pyralus, ×Sorbaronia (Malinae, Rosaceae) не были действительно обнародованы, поскольку в качестве типов для каждого таксона были обозначены два или три сбора. Осуществлено действительное обнародование названий ×Sorbaronia kovalevii Mezhenskyj, ×Cydolus rudenkoana Mezhenskyj, ×Pyralus kursakovii Mezhenskyj с указанием одного сбора, определенного как голотип для каждого нотовида.